2015
DOI: 10.1155/2015/971697
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Akt and SGK1 in the Regulation of Renal Tubular Transport

Abstract: A serine/threonine kinase Akt is a key mediator in various signaling pathways including regulation of renal tubular transport. In proximal tubules, Akt mediates insulin signaling via insulin receptor substrate 2 (IRS2) and stimulates sodium-bicarbonate cotransporter (NBCe1), resulting in increased sodium reabsorption. In insulin resistance, the IRS2 in kidney cortex is exceptionally preserved and may mediate the stimulatory effect of insulin on NBCe1 to cause hypertension in diabetes via sodium retention. Like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…It is well established that the PI3K/Akt/mTOR pathway is capable of activating SGK-1, the primary regulator of α-ENaC. [ 32 , 33 ] We have also previously shown that PRR is capable of activating the PI3K/Akt/mTOR pathway under high glucose conditions. [ 34 ] In the previously mentioned study by Ramkumar et al, prorenin stimulated α-ENaC expression in a PRR dependent manner and this was prevented by inhibition of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the PI3K/Akt/mTOR pathway is capable of activating SGK-1, the primary regulator of α-ENaC. [ 32 , 33 ] We have also previously shown that PRR is capable of activating the PI3K/Akt/mTOR pathway under high glucose conditions. [ 34 ] In the previously mentioned study by Ramkumar et al, prorenin stimulated α-ENaC expression in a PRR dependent manner and this was prevented by inhibition of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, kinase-mediated transporter regulation was revealed in the renal system. Renal tubular transport and reabsorption of water and electrolytes are regulated by two kinases, serine/threonine kinase Akt and serum-/glucocorticoid-inducible kinase 1 (SGK1), increasing Na + reabsorption [19]. Signaling pathways involving the phosphorylation of Akt enhance activities of NBCe1, ENaC, and Na + -Cl − cotransporter (NCC), and those involving SGK1 promote NHE3 activation, encouraging reabsorption of Na + .…”
Section: Convergent Regulation Of Ion Homeostasismentioning
confidence: 99%
“…Signaling pathways involving the phosphorylation of Akt enhance activities of NBCe1, ENaC, and Na + -Cl − cotransporter (NCC), and those involving SGK1 promote NHE3 activation, encouraging reabsorption of Na + . SGK1, furthermore, increases K + secretion via the renal outer medullary potassium channel (ROMK) [19]. Major modulation of electrolyte transport occurs in the renal and exocrine systems, including salivary glands and pancreatic glands, and has already been extensively discussed [5,20].…”
Section: Convergent Regulation Of Ion Homeostasismentioning
confidence: 99%
“…This raises the possibility that there is molecular crosstalk between the PTH and FGF23 signalling pathways 4 , 163 . Although PKA and PKC seem to be the predominant signalling mechanisms for PTH, they also activate the MAPK pathway, which is activated by FGF23 binding the FGFR 160 , 164 , 165 . Interestingly, the downstream effects of PTH (that is, internalization of NaPi-IIa) were only partially abolished by PKA and PKC inhibition, but inhibition of MAPK completely abolished NaPi-IIa internalization 142 .…”
Section: Integration Of Parathyroid Hormone and Fibroblast Growth Facmentioning
confidence: 99%